Agriculture census based dynamics of changes in livestock farming of Bangladesh-A review (Bangladesh Journal of Animal Science, 2016)
The present work was undertaken to determine the dynamics of changes taken place in farm animal production system of Bangladesh transmuting gradually on a cusp of increasing feed and food competition and gaining competitive advantages in domestic production of milk, meat and eggs. The data available from livestock population of the Agricultural Census of 1960 and of 1977, Agricultural and Livestock Census of 1983-84, the census of agriculture 2008 and the livestock and poultry survey of 2009 were used to figure out quantitative changes and extrapolate inherent causes of them. During the period of 1960 to 2009 human population increased at a faster pace (55.2 million to 144.0 million) than livestock population (10.5 to 17.0 livestock units). The later may be explained by a reduction of per capita availability of bovine animals (0.38 in 1960 to 0.18 in 2009) while the same for small ruminants remained similar (0.12 to 0.12, respectively), and that of poultry increased from 0.65 to 1.07, respectively. However, over the decade dairy farming, cattle fattening and commercial poultry supported increased production of livestock products. The ratio of total cows to adult male cattle of 0.56 in 1960 increased to 0.88 in 1977 reflecting farmers` interest on dairying, and the trend was being continued till 2009. Farm animal population at medium and large farms decreased over the period significantly (P